2022
DOI: 10.1136/bmjopen-2021-058749
|View full text |Cite
|
Sign up to set email alerts
|

Equity of timely access to liver and stomach cancer surgery for Indigenous patients in New Zealand: a national cohort study

Abstract: ObjectivesWhen combined, liver and stomach cancers are second only to lung cancer as the most common causes of cancer death for the indigenous Māori population of New Zealand—with Māori also experiencing substantial disparities in the likelihood of survival once diagnosed with these cancers. Since a key driver of this disparity in survival could be access to surgical treatment, we have used national-level data to examine surgical procedures performed on Māori patients with liver and stomach cancers and compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In New Zealand, 17.1% of the population is Māori ( 91 ), however, zero participants in our study self-identified as Māori. Compared to non-Māori, Māori patients in general face delayed treatment ( 92 ), lower life expectancies ( 93 ) and worse health outcomes ( 94 , 95 ) in the New Zealand health system. Currently, there are no published studies that assess the perceptions and experiences of diagnosis and care of Māori cohorts experiencing endometriosis (mate kirikopu).…”
Section: Discussionmentioning
confidence: 99%
“…In New Zealand, 17.1% of the population is Māori ( 91 ), however, zero participants in our study self-identified as Māori. Compared to non-Māori, Māori patients in general face delayed treatment ( 92 ), lower life expectancies ( 93 ) and worse health outcomes ( 94 , 95 ) in the New Zealand health system. Currently, there are no published studies that assess the perceptions and experiences of diagnosis and care of Māori cohorts experiencing endometriosis (mate kirikopu).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of disparities between M aori and European patients with lung cancer in the timing of surgery and systemic therapy is reassuring, particularly considering the additional barriers that M aori patients need to overcome to access these treatments (including being more likely to live in deprivation and outside of urban centers where these treatments are delivered). We recently showed that M aori patients needed to travel twice as far to access surgery for liver cancer, 21 and yet there were no differences in the timing of surgery relative to diagnosis, 22 suggesting significant resilience by M aori patients in terms of overcoming these barriers. In this study, we noted that M aori patients appeared less likely to access radiation therapy in the first 4 weeks of diagnosis and correspondingly more likely to access it 4-12 weeks postdiagnosis.…”
Section: Similar To Radiation Therapy Mmentioning
confidence: 99%
“…When compared with non-Māori, Māori patients face delayed treatments [23], lower life expectancies [24] and worse health outcomes [25][26][27][28] in the New Zealand health system. Racial discrimination, whether intentional or unconscious, against Māori people is associated with poorer health outcomes, reduced access to healthcare, negative impacts on mental health, and poorer life satisfaction [29,30].…”
Section: Endometriosis and Māorimentioning
confidence: 99%